High-Definition transcranial direct current stimulation in early onset epileptic encephalopathy: a case study. (2nd January 2018) - Meiron, Oded; Gale, Rena; Namestnic, Julia; Bennet-Back, Odeya; David, Jonathan; Gebodh, Nigel; Adair, Devin; Esmaeilpour, Zeinab; Bikson, Marom
ABSTRACT: Primary objective: Early onset epileptic encephalopathy is characterized by high daily seizure-frequency, multifocal epileptic discharges, severe psychomotor retardation, and death at infancy. Currently, there are no effective treatments to alleviate seizure frequency and high-voltage epileptic discharges in these catastrophic epilepsy cases. The current study examined the safety and feasibility of High-Definition transcranial direct current stimulation (HD-tDCS) in reducing epileptiform activity in a 30-month-old child suffering from early onset epileptic encephalopathy. Design and Methods: HD-tDCS was administered over 10 intervention days spanning two weeks including pre- and post-intervention video-EEG monitoring. Results: There were no serious adverse events or side effects related to the HD-tDCS intervention. Frequency of clinical seizures was not significantly reduced. However, interictal sharp wave amplitudes were significantly lower during the post-intervention period versus baseline. Vital signs and blood biochemistry remained stable throughout the entire study. Conclusions: These exploratory findings support the safety and feasibility of 4 × 1 HD-tDCS in early onset epileptic encephalopathy and provide the first evidence of HD-tDCS effects on paroxysmal EEG features in electroclinical cases under the age of 36 months. Extending HD-tDCS treatment may enhance electrographic findings and clinical effects.